(3RZd GdYdes - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3CYde Cf ai cd WGFaI ef YdeGA GdCeI eGjPe hjYGH aJLfHg s
(3BNQgG (B:s
(3heJi cGf GdhGYX eKd GdMSf hGdTjN YHO GdbGOQ GdLjdGfi QMegeG Gddg JYGdi JfaY Hg GdfGS JeJ GdfSNI GdcQjeI s
(3cJHJ Yf fSNI HNW UGdM GdUOjb GdfeGRi cJHJ HYV cdeGJgG HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs